Firlianty, Hermansyah, Windarina Samosir: KAJIAN EFEKTIVITAS EKSTRAK GEL IKAN TOMAN (Channa micropeltes) PADA LUKA BAKAR MENCIT (Mus musculus) - Agrienvi (Agrienvi: Jurnal Ilmu Pertanian, 2020)
This study aims to know the effectivity of snakehead (Channa micropeltes) gel extract on the burns healing ofrat (Mus musculus). It was carried out for 4 months, September 2018 to January 2019. The study employed anexperimental method of Complete Randomized Design with 4 treatmnets and 3 replications. Treatment A wascontrol, B used 1.5% gel extract of C. micropeltes, C used 3 %, and D used 4.5%, respectively. Results revealed thatin day-4, 8 and 12 the administration of gel extract of C. micropeltes gave significant effect on the burns healing of rat(Mus musculus) (Fcalc.> Ftab., 0.05).Keywords : gel extract, Channa micropeltes, rat Mus musculus, burns healing